Ubac and me : a life of love and adventure with a French mountain dog - Sapin-Defour, Cédric, 1975- (Summit Books, an imprint of Simon & Schuster, LLC, 2025)
"A tiny ad in a local newspaper catches Cédric Sapin-Defour's eye: a litter of Bernese Mountain Dog puppies need homes. A lonely, single, gym teacher and mountain climber in the French Alps, Cédric visits the dogs and immediately falls for the puppy with a blue collar who steps over his siblings to get to him. Named Ubac for the north side of the mountain -- the rainy, cloudy slope -- the puppy upends Cédric's life. They go on hikes together, taking to the hills and exploring, forging a bond that brings joy and a sense of fulfillment and adventure. They brave the world together, hate to be apart, and crave the mountains and the nature; they protect each other. Over the course of thirteen years, their pack expands to include Mathilde, Cédric's wife, and even more dogs. A dog named for the rainy side of the mountain is an inspiring lesson in how walking the rocky, cloudy hills together can bring the greatest light and the sunniest joys, even if the shared journey is short. Ubac and Me is an intimate meditation on the transformative power of unconditional love."--